CROP FERTILIZER USE EFFICIENCY ANALYSIS (CFE): A Tool in identifying appropriate planting materials of coconut in different agro climatic conditions - S.S. MAGAT S.S. MAGAT (International Coconut Community Journal, 1996)
Nine (9) sites with different growing conditions used in the Regional Testing of Promising Coconut Hybrids and Cultivars in the Philippines or MULTILOC Project (1985‑1996) was subjected to the Crop Fertilizer Use Efficiency (CFE) Analysis. Two CFE indices were used CFEn = nut yield/kg fertilizer applied (per tree) and CFE X = kg copra yield kg fertilizers applied (per tree). To a great extent, crop fertilizer use efficiency (CFE) ofsuperior hybrids grown in similar environments and appied with same moderate rates offertilizers have higher efficiency of converting the appliedfertilizers to economic yield, nuts or copra (measured in terms of CFEn and CFEc) compared to tall varielies tested in all MULTILOC sites (dry, intermediate and wet growing zone) at n ine years ftom field‑planting (FP). The CFEs, CFEn (nut‑based) at nine sites clearly differed in ternu of the first (best) five entries with highest CFE values. Explanation for this observation deserves further study, looking into the relationship of hybrid vigour (heterosis), crop morphology, physiology and yield.